Long‐term variations of ultraviolet radiation in Tibetan Plateau from observation and estimation. (8th July 2014) - Peng, Simao; Du, Qingyun; Wang, Lunche; Lin, Aiwen; Hu, Bo
ABSTRACT Measurements of ultraviolet radiation (UV) and global solar radiation (G) in Lhasa, Tibetan Plateau, from 2006 to 2012 were used to investigate their seasonal characteristics. The maximum UV irradiation and UV fraction (percentage of UV compared to G, FUV) occurred at noon in summer (July) and the minimum values occurred in winter (December); the annual means of UV and FUV were approximately 0.91 MJ m−2 day−1 and 4.3%, respectively. By analysing the dependence of UV irradiances on clearness index (Kt) and cosine of the solar zenith angle, an efficient all‐sky model was developed for estimating UV radiation in Tibetan Plateau. The model was tested at Sanjiang and Donghu stations and produced satisfactory estimates. UV dataset was then reconstructed from G using the newly developed model for the period 1961–2012. It was discovered that annual mean daily UV irradiation was approximately 0.89 MJ m−2 day−1 and there was a significant decreasing trend (at the rate of 0.013 MJ m−2 decade−1) over the last 50 years in the Tibetan Plateau. The largest decrease occurred in autumn (−0.023 MJ m−2 decade−1) and a small decrease observed in summer. Meanwhile, results also revealed that UV radiation increased at 0.05 MJ m−2 year−1 from 1989 to 2012, which was inconsistent with the variations of G in the study area. The proposed all‐weather UV model is very important for ecological modelling, atmospheric environment, agricultural processes and solar energy applications in the Tibetan Plateau, China.